Cover Feature: Broadband‐Emitting 2 D Hybrid Organic–Inorganic Perovskite Based on Cyclohexane‐bis(methylamonium) Cation (ChemSusChem 19/2017). Issue 19 (2nd October 2017) - Neogi, Ishita; Bruno, Annalisa; Bahulayan, Damodaran; Goh, Teck Wee; Ghosh, Biplab; Ganguly, Rakesh; Cortecchia, Daniele; Sum, Tze Chien; Soci, Cesare; Mathews, Nripan; Mhaisalkar, Subodh Gautam
Abstract : The Cover Feature shows the stereoisomeric structures of a white‐light emitting layered hybrid perovskite based on the cis ‐1, 3‐bis(methylaminohydrobromide)cyclohexane core. Layered hybrid perovskites are of interest as they are solution‐processable materials with potential for cost‐effective lighting and displays. In addition, their broadband emission is related to the formation of intra‐band color centers. The photoluminescence of the material presented here shows a strong dependence on the stereoisomerism of the core cation. More information can be found in the Full Paper by Neogi et al onpage 3765 in Issue 19, 2017 (DOI:10.1002/cssc.201701227 ).